Natural products, an important resource for discovery of multitarget drugs and functional food for regulation of hepatic glucose metabolism - Li J; Yu H; Wang S; Wang W; Chen Q; Ma Y; Zhang Y; Wang T (Dove Medical Press, 2018)
Jian Li,1,* Haiyang Yu,2,* Sijian Wang,1 Wei Wang,3 Qian Chen,1 Yanmin Ma,2 Yi Zhang,1 Tao Wang1 1Tianjin State Key Laboratory of Modern Chinese Medicine, Tianjin, 2Department of Phytochemistry, Institute of Traditional Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, China; 3Internal Medicine, Houston Methodist Hospital, Houston, TX, USA *These authors contributed equally to this work Abstract: Imbalanced hepatic glucose homeostasis is one of the critical pathologic events in the development of metabolic syndromes (MSs). Therefore, regulation of imbalanced hepatic glucose homeostasis is important in drug development for MS treatment. In this review, we discuss the major targets that regulate hepatic glucose homeostasis in human physiologic and pathophysiologic processes, involving hepatic glucose uptake, glycolysis and glycogen synthesis, and summarize their changes in MSs. Recent literature suggests the necessity of multitarget drugs in the management of MS disorder for regulation of imbalanced glucose homeostasis in both experimental models and MS patients. Here, we highlight the potential bioactive compounds from natural products with medicinal or health care values, and focus on polypharmacologic and multitarget natural products with effects on various signaling pathways in hepatic glucose metabolism. This review shows the advantage and feasibility of discovering multicompound–multitarget drugs from natural products, and providing a new perspective of ways on drug and functional food development for MSs. Keywords: hepatic glucose metabolism, natural products, multitarget, metabolic syndromes, drug and functional food development integrative medicine